2017
DOI: 10.1097/gme.0000000000000784
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Chinese version of the Menopause-Specific Quality-of-Life questionnaire

Abstract: Objective:The Menopause-Specific Quality-of-Life (MENQOL) questionnaire was developed as a specific tool to measure the health-related quality-of-life of postmenopausal women. Thus far, the Chinese version questionnaire has not been subjected to psychometric assessment with a large sample. This study aims to evaluate the validity and reliability of the Chinese version of the MENQOL specific to postmenopausal women in China.Methods:A total of 1,137 menopausal symptomatic and 491 menopausal asymptomatic women fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 19 publications
7
23
0
1
Order By: Relevance
“…In fact, most participants (N=267) did not have facial hair increase as well as the mean score of the item was rather low (0.18), indicating that it was rarely seen or a very mild symptom in the participants included in this study. This is consistent with published literature that "increased facial hair" and "weight gain" are not prevalent in Asian women (Chen, Lin, Wei, Gao, & Wu, 2007;Nie, Yang, Liu, Zhao, & Wang, 2017;Yim et al, 2015). In particular, Nie et al (2017) reported that the low incidence of increased facial hair in Chinese women is difficult to explain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In fact, most participants (N=267) did not have facial hair increase as well as the mean score of the item was rather low (0.18), indicating that it was rarely seen or a very mild symptom in the participants included in this study. This is consistent with published literature that "increased facial hair" and "weight gain" are not prevalent in Asian women (Chen, Lin, Wei, Gao, & Wu, 2007;Nie, Yang, Liu, Zhao, & Wang, 2017;Yim et al, 2015). In particular, Nie et al (2017) reported that the low incidence of increased facial hair in Chinese women is difficult to explain.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with published literature that "increased facial hair" and "weight gain" are not prevalent in Asian women (Chen, Lin, Wei, Gao, & Wu, 2007;Nie, Yang, Liu, Zhao, & Wang, 2017;Yim et al, 2015). In particular, Nie et al (2017) reported that the low incidence of increased facial hair in Chinese women is difficult to explain. Therefore, we decided to remove this item.…”
Section: Discussionsupporting
confidence: 91%
“…Discriminant validity was measured by comparison of menopausal symptomatic and asymptomatic women for each item [ 18 ], compared with independent sample t test. Asymptomatic and symptomatic women in this study were based on the severity of menopausal symptoms; absence of symptoms and mild symptoms in five-point Likert scale (0–1) were considered as asymptomatic and other severities (2–4 in Likert scale) were taken as symptomatic women.…”
Section: Methodsmentioning
confidence: 99%
“…The overall prevalence was 50.2% (total of 1,691 women), which was lower than the prevalence reported by Nie et al (80.7%) and consistent with the results of our previous study. 33 …”
Section: Discussionmentioning
confidence: 99%